Low-voltage-driven conductive hydrogel as well as preparation method and application thereof
By forming positively charged nanoemulsion microspheres and multicomponent non-covalent crosslinking systems in the conductive hydrogel, using electric field to induce electrostatic repulsion and hydrogen bond interactions, a low voltage-driven conductive hydrogel was developed, solving the problems of high voltage demand and low delivery efficiency in the prior art, and achieving rapid and controlled release of a variety of guest molecules.
Patent Information
- Application Number
- CN202411719408.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
Existing conductive hydrogels require high voltages in electrically stimulating drug delivery systems to achieve effective drug release and have problems with low delivery efficiency and limitations on specific molecules.
A low voltage driven conductive hydrogel was developed to form positively charged nanoemulsion microspheres by combining a mixed solution of quaternary ammonium chitosan, guest molecules and water with a mixture of emulsifiers and greases, and a multicomponent non-covalent crosslinking system was formed using PVA and PEDOT:PSS to induce electrostatic repulsion and hydrogen bond interaction between the gel body and the guest molecules through an electric field, achieving rapid and controllable molecular delivery.
The conductive hydrogel can achieve rapid and controlled release of a variety of guest molecules at voltages as low as 1.5V, with cumulative release rates of DOX and RB reaching 44.72% and 48.32%, respectively, and show superior self-healing properties and conductivity, suitable for tissue engineering and drug delivery.
Smart Images

Figure CN119529484A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a low-voltage driven conductive hydrogel and a preparation method and application thereof. Background Art
[0002] Advances in precision medicine and personalized drug therapy have driven the development of stimuli-responsive drug delivery systems, which are designed to produce and regulate the effects of drug delivery based on changes in the environment, allowing them to be designed on demand. Stimuli-responsive hydrogels have attracted widespread attention due to their adjustable structure, good biodegradability, and strong versatility. They can undergo controllable property changes under external physical (such as temperature, pressure, electric and magnetic fields) or chemical (pH, enzyme) stimuli. Therefore, stimuli-responsive hydrogels are widely used in cutting-edge scientific and technological fields such as electronic skin, soft robots, implantable biomedical devices, and drug delivery.
[0003] In recent years, people have made great efforts to design and construct electrostimulant drug delivery systems because of their controllability, high efficiency and reversibility. Therefore, researchers have prepared a variety of conductive hydrogels using different conductive materials through different synthesis strategies. The public document Electro-Responsive Conductive Blended Hydrogel Patch provides a conductive hydrogel, and the mixed gel patch obtained by mixing alginate, methacryloyl gelatin and silver nanowires has controllable drug release at a voltage of 3V, and the release amount of doxorubicin is 57%. The public document Electrochemical and Nanostructural Characterization of Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)Films as Coatings for Neural Electrodes provides a conductive injectable tetraphenylamine grafted polysaccharide / xanthan gum / sodium trimetaphosphate hydrogel, which has good conductivity and stretchability at a voltage of 3V and has electroresponsive drug release behavior. In addition, the open document Electro-stimulated Drug Release by Methacrylated Hyaluronic Acid-based Conductive Hydrogel with Enhanced Mechanical Properties provides a conductive hyaluronic acid / graphene / polyaniline hydrogel, which has an electrically stimulated drug release behavior at a voltage of 0 to 3 V. In order to improve the electrochemical durability, there is an urgent need for a drug delivery conductive hydrogel with low voltage drive.
[0004] The rise of functional polymers has promoted the development of molecular delivery systems. Hydrogels have significant advantages due to their encapsulation ability. Traditional hydrogels achieve effective delivery under electrical stimulation by swelling, deswelling or degradation, but this process usually requires high voltage. Therefore, their application in many occasions is limited. In contrast, some conductive polymers, such as polypyrrole (PPy) and polyaniline (PANI), have attracted widespread attention due to their high conductivity and unique molecular structure. However, they usually rely on redox processes to achieve electric field controlled release, which is prone to side reactions, chemical accumulation and difficult-to-control release kinetics. Therefore, there is a need for an electrical stimulation responsive controlled release system that can be manipulated by a completely physical mechanism to achieve rapid but controllable and safe delivery. Based on a variety of stimulus response modes, the electrical stimulation molecular delivery system has the characteristics of being more controllable, efficient and reversible, so conductive hydrogels have broad prospects in the field of molecular delivery. However, when the current conductive hydrogels are applied to molecular delivery, they have low delivery efficiency, require higher voltages to achieve large release amounts, and are very restrictive to specific molecules. In addition, "charge interruption" is prone to occur, resulting in delivery being affected.
[0005] Therefore, constructing a conductive hydrogel delivery system that is self-healing, biosafe, capable of loading a variety of guest molecules, and can achieve rapid and controllable release has become one of the urgent problems to be solved. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a low-voltage driven conductive hydrogel and its preparation method and application. The conductive hydrogel can achieve rapid and controlled release of a variety of guest molecules at a voltage as low as 1.5V, and the cumulative release rates of DOX (doxorubicin) and RB (rhodamine B) reach 44.72% and 48.32%, respectively.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The present invention provides a low-voltage driven conductive hydrogel, wherein the raw materials of the conductive hydrogel include the following components in percentage by weight:
[0009]
[0010] Furthermore, the guest molecule is selected from any one of a luminescent molecule, a drug or an organic fluorescent probe.
[0011] Furthermore, the luminescent molecule is hexa(4-carboxy-1-phenylthio)benzene (HCPB) or sodium tetraphenylethylene sulfonate; the drug is selected from any one of doxorubicin (DOX), oxacillin or acyclovir; and the organic fluorescent probe is selected from any one of rhodamine B (RB), fluorescein isothiocyanate or methylene blue.
[0012] Furthermore, the emulsifier is selected from at least one of Tween-80, Span-80, sodium lauryl sulfate or polyoxyethylene stearate.
[0013] Furthermore, the oil is selected from any one of soybean oil, sunflower oil, almond oil or coconut oil.
[0014] In another aspect, the present invention also provides a method for preparing a low-voltage driven conductive hydrogel as described above, comprising the following steps:
[0015] S1, uniformly mixing the emulsifier and the oil, then slowly adding a mixed solution of quaternary ammonium salt chitosan, guest molecules and a portion of water into the mixture of the emulsifier and the oil, stirring, ultrasonicating and standing to obtain a positively charged guest molecule nanoemulsion microsphere solution;
[0016] S2, completely dissolving the PVA powder in another portion of water to obtain a PVA aqueous solution, adding PEDOT:PSS and the guest molecule nanoemulsion microsphere solution obtained in step S1 to the PVA aqueous solution after cooling to room temperature, mixing evenly to form a conductive hydrogel precursor, adding Na2B4O7 for chemical cross-linking and then standing, and then cyclically freezing and thawing to obtain a low-voltage driven conductive hydrogel.
[0017] Furthermore, in step S2, the PVA powder is completely dissolved in water at a temperature of 80°C to 100°C.
[0018] Furthermore, the mass ratio of the water used to dissolve the quaternary ammonium salt chitosan and the guest molecules in step S1 to the water used to dissolve the PVA powder in step S2 is 1:(2.5-3.5).
[0019] Furthermore, in step S2, the freeze-thaw cycle is specifically as follows: the stationary chemically cross-linked conductive hydrogel precursor is frozen at -40°C to -20°C for 4 to 12 hours, then taken out and thawed at a temperature not lower than 20°C for 2 to 4 hours, and the freeze-thaw process is repeated 3 to 5 times.
[0020] In a third aspect, the present invention also provides an application of any of the above-mentioned low-voltage driven conductive hydrogels in tissue engineering and drug delivery. For example, the conductive hydrogel of the present invention can be used to controllably deliver a series of guest molecules, including luminescent molecules (such as HCPB), drugs (such as DOX) and fluorescent probes (such as RB), and the delivery of guest molecules is not limited by specific materials or guest molecules.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention provides a low-voltage driven conductive hydrogel and its preparation method and application. By using low voltage to manipulate the non-covalent interaction between the components of the conductive hydrogel, a conductive hydrogel for rapid and controllable molecular delivery is established. Specifically, the conductive hydrogel uses the electric field to induce the electrostatic repulsion between the gel body and the guest molecules and the dynamic changes of the hydrogen bond interactions within the conductive hydrogel to achieve efficient and controllable guest molecule transmission. A voltage as low as 1.5V is sufficient to affect this multi-component non-covalent cross-linked system, reversibly induce its pore size to increase, and can achieve 39% to 48% of rapid and controllable guest molecule release within 2 hours. In addition, the conductive hydrogel of the present invention can quickly and controllably release various guest molecules, including luminescent molecules, drugs and fluorescent probes, and the delivery of guest molecules is not limited by specific materials or guest molecules, and has broad application prospects in the fields of tissue engineering and drug delivery.
[0023] (2) Since nanoemulsions (NEs) are easy to prepare and can accommodate guest molecules without size restrictions. The present invention first prepares positively charged nanoemulsion (QCSNE) microspheres to lay a structural foundation for loading guest molecules; then polyvinyl alcohol (PVA) is used as a hydrogel matrix, poly (3,4-ethylenedioxythiophene): (polystyrene sulfonate) (PEDOT:PSS, or simply P:P) is used as a conductive additive, and a multi-component non-covalent cross-linked system PVA-P:P conductive hydrogel is formed through borate cross-linking and freeze-thaw cycles; since PSS is hydrophilic in the P:P structure and PEDOT is hydrophobic, the outside of the P:P polymer chain is negatively charged, so that the QCSNE microspheres are loaded through electrostatic interactions, and the guest molecules are loaded into the cavity of the QCSNE microspheres to obtain (Guest) QCSNE@PVA-P:P conductive hydrogel, and the presence of P:P will stabilize the release of guest molecules through electrostatic attraction. On the one hand, the crosslinking density of (Guest) QCSNE@PVA-P:P conductive hydrogel is adjusted by hydrogen bonding interaction between the sulfonic acid groups of PSS in P:P and the hydroxyl groups in PVA, thereby adjusting the pore size; on the other hand, the electric field affects the multi-component non-covalent crosslinking inside the (Guest) QCSNE@PVA-P:P conductive hydrogel, inducing reversible pore size expansion to facilitate the release of guest molecules. In the present invention, the luminescent molecule hexa(4-carboxyl-1-phenylthio)benzene (HCPB), the anticancer drug doxorubicin (DOX) or the organic fluorescent probe rhodamine B (RB) are loaded into the QCSNE@PVA-P:P conductive hydrogel as different types of guest molecules. The controlled release of these guest molecules shows similar release kinetics, highlighting the universality of the strategy of the present invention.
[0024] (3) The (Guest) QCSNE@PVA-P:P conductive hydrogel of the present invention has good conductivity, machinability and stability, and also shows excellent self-healing properties. It still has high conductivity after self-healing and can function effectively at significantly lower voltages (0.5-3V), and has significant advantages in the controlled delivery of molecules in low-voltage areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1The structure and morphology characterization diagrams of NE, QCSNE, PVA-P:P and QCSNE@PVA-P:P in Example 1 of the present invention, wherein (a) is a DLS diagram, (b) is a Zeta potential, (c) is a TEM image of (i) NE and (ii) QCSNE, (d) is a SEM image of PVA (3wt%) hydrogel, (e) is a SEM image of PVA (3wt%)-P:P (15wt%), (f) is a FTIR spectrum of PVA, P:P, and PVA-P:P, and (g) is a FTIR spectrum of QCS, NE, QCSNE and QCSNE@PVA:PP;
[0026] Figure 2 These are SEM images of freeze-dried PVA and PVA-P:P hydrogels of different concentrations in Example 1 of the present invention, wherein (a) is a SEM image of PVA (8 wt%), (b) is a SEM image of PVA (8 wt%)-P:P (15 wt%), (c) is a SEM image of PVA (7 wt%), (d) is a SEM image of PVA (7 wt%)-P:P (15 wt%), (e) is a SEM image of PVA (6 wt%), (f) is a SEM image of PVA (6 wt%)-P:P (15 wt%), (g) is a SEM image of PVA (5 wt%), (h) is a SEM image of PVA (5 wt%)-P:P (15 wt%), (i) is a SEM image of PVA (4 wt%), and (j) is a SEM image of PVA (4 wt%)-P:P (15 wt%);
[0027] Figure 3 Graphs showing the self-healing and conductive properties of the PVA-P:P hydrogel in Example 1 of the present invention, wherein (a) is a digital photograph of the PVA (3 wt %) (transparent) and PVA (3 wt %) -P:P (15 wt %) (dark blue) hydrogels after being merged, (b) is a micrograph of the hydrogel self-healing process (scale: 1 μm), (c) is the conductivity of the hydrogels with different P:P concentrations and the strain and modulus at the flow point, (d) is the EIS of the hydrogels with different P:P concentrations, (e) is the CSC of the hydrogels with different P:P concentrations, (f) is the current change before and after the hydrogel is cut, (g) is a digital photograph of the effect of the hydrogel on the circuit after breaking and self-healing, and (h) is a digital photograph of the effect of the (HCPB)QCSNE@PVA (3 wt %) -P:P (15 wt %) hydrogel on the circuit after breaking and self-healing;
[0028] Figure 4: The results of the electric field-controlled release of guest molecules in Example 1 of the present invention, wherein (a) is the release of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at a voltage of 1.5V or 0V (the inset is the chemical structure of HCPB), (b) is the ON / OFF voltage release curve of (HCPB)QCSNE@PVA(3wt%) and (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at an interval of 20 minutes, (c) is a brief comparison of the molecular release curves of different hydrogels after 120 minutes of electrical stimulation, and (d) is the release curve of (HCPB)QCSNE@PVA(3wt%)-P:P at an interval of 10 minutes. In situ Raman spectra of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel under 1.5V electric field, (e) is the relative ratio change of hydrogen bond signal (corresponding to the change of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel when 1.5V voltage is alternately applied for 10 minutes and turned off for 10 minutes), (f) is the SEM image of freeze-dried PVA(3wt%)-P:P(15wt%) after (i) no application and (ii) application of 1.5V voltage for 120 minutes when 1.5V voltage is applied, (g) is the pore size distribution histogram of PVA(3wt%)-P:P(15wt%) when voltage is applied / not applied, (h) is the in situ Raman shift change of SO in repeated electrical stimulation cycles;
[0029] Figure 5 The UV-Vis spectra of different HCPB concentrations (using PBS as the solvent) and the corresponding HCPB concentration-absorbance standard curve in Example 1 of the present invention, wherein (a) is the UV-Vis spectra of different HCPB concentrations (using PBS as the solvent), and (b) is the HCPB concentration-absorbance standard curve;
[0030] Figure 6 (a) release curve and (b) Korsmeyer-Peppas fitting curve of (HCPB)QCSNE@PVA (3 wt%) hydrogel at 0 V in Example 1 of the present invention;
[0031] Figure 7 Korsmeyer-Peppas fitting curve of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V / 0V in Example 1 of the present invention;
[0032] Figure 8The UV-visible spectra of different concentrations of DOX and RB (PBS as solvent) and the concentration-absorbance standard curve of DOX and RB in Example 1 of the present invention, wherein (a, c) are the UV-visible spectra of different concentrations of DOX and RB (PBS as solvent), and (b, d) are the concentration-absorbance standard curves of DOX and RB;
[0033] Fig. 9 Release curves of (DOX)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel and (RB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V and their Korsmeyer-Peppas fitting curves in Example 1 of the present invention, wherein (a) is the release curve of (DOX)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V, (b) is the release curve of (RB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V, and (c) is the Korsmeyer-Peppas fitting curve of (a) and (b). DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0035] The present invention provides a low-voltage driven conductive hydrogel, wherein the raw materials of the conductive hydrogel include the following components in percentage by weight:
[0036]
[0037] The guest molecule is selected from any one of a luminescent molecule, a drug or an organic fluorescent probe. The luminescent molecule is hexa(4-carboxyl-1-phenylthio)benzene (HCPB) or sodium tetraphenylethylene-sulfonate; the drug is selected from any one of doxorubicin (DOX), oxacillin or acyclovir; the organic fluorescent probe is selected from any one of rhodamine B (RB), fluorescein isothiocyanate or methylene blue. The emulsifier is selected from at least one of Tween-80, Span-80, sodium dodecyl sulfate or polyoxyethylene stearate. The oil is selected from any one of soybean oil, sunflower oil, almond oil or coconut oil.
[0038] The low voltage driven conductive hydrogel is prepared by the following method:
[0039] S1, uniformly mixing the emulsifier and the oil, then slowly adding a mixed solution of quaternary ammonium salt chitosan, guest molecules and a portion of water into the mixture of the emulsifier and the oil, stirring, ultrasonicating and standing to obtain a positively charged guest molecule nanoemulsion microsphere solution;
[0040] S2, completely dissolving PVA powder in another part of water at a temperature of 80°C to 100°C to obtain a PVA aqueous solution, adding PEDOT:PSS and the guest molecule nanoemulsion microsphere solution obtained in step S1 to the PVA aqueous solution after cooling to room temperature, mixing evenly to form a conductive hydrogel precursor, adding Na2B4O7 for chemical cross-linking, and then standing, then freezing the chemically cross-linked conductive hydrogel precursor at -40°C to -20°C for 4 to 12 hours, then taking it out and thawing it at a temperature not lower than 20°C for 2 to 4 hours, and repeating the freezing-thawing process 3 to 5 times to obtain a low-voltage driven conductive hydrogel.
[0041] The mass ratio of the water used to dissolve the quaternary ammonium salt chitosan and the guest molecules in step S1 to the water used to dissolve the PVA powder in step S2 is 1:(2.5-3.5).
[0042] The resulting low-voltage driven conductive hydrogel can be used for tissue engineering and drug delivery. For example, the conductive hydrogel of the present invention can be used to controllably deliver a series of guest molecules, including luminescent molecules (such as HCPB), drugs (such as DOX) and fluorescent probes (such as RB), and the delivery of guest molecules is not limited to specific materials or guest molecules.
[0043] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available. For example, polyvinyl alcohol (PVA, molecular weight: 89-98kDa, alcoholysis degree 99%) and sodium tetraborate (Na2B4O7) are purchased from Aldrich. PEDOT:PSS (model CleviosPH1000) is purchased from Heraeus. Soybean oil (pharmaceutical grade), Tween-80 (pharmaceutical grade) and Span-80 (pharmaceutical grade) are purchased from Sigma-Aldrich. Chitosan quaternary ammonium salt (quaternization degree 90%) is purchased from Shanghai Yuanye Biotechnology Co., Ltd. Hexafluorobenzene (C6F6) and methyl 4-mercaptobenzoate (C8H8O2S) are purchased from Beijing Huawei Ruike Chemical Co., Ltd. N,N-Dimethylformamide (DMF), hydrochloric acid (HCl), tetrahydrofuran (THF), doxorubicin (DOX), and rhodamine B (RB) were purchased from Adamas.
[0044] Example 1
[0045] (1) Preparation of nanoemulsion (NE) microspheres:
[0046] 2.28 g of Tween-80 and 4.55 g of Span-80 were mixed as emulsifiers, 2.28 g of soybean oil was added as the oil phase, and the mixture was stirred at 450 rpm for 15 minutes. Subsequently, 0.890 mL of deionized water was added dropwise, the mixture was stirred at 800 rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain nanoemulsion (NE) microspheres.
[0047] (2) Preparation of quaternary chitosan modified nanoemulsion (QCSNE) microspheres:
[0048] 2.28 g of Tween-80 and 4.55 g of Span-80 were mixed as emulsifiers, 2.28 g of soybean oil was added as the oil phase, and the mixture was stirred at 450 rpm for 15 minutes. Subsequently, 0.662 mL of deionized water and 0.228 g (10 wt%) of chitosan quaternary ammonium salt (QCS) solution were added dropwise, the mixture was stirred at 800 rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain chitosan quaternary ammonium modified nanoemulsion (QCSNE) microspheres.
[0049] (3) Preparation of (3 wt%) PVA-P:P hydrogel:
[0050] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to obtain a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken and 0, 0.062, 0.198, 0.353 and 0.667 mL of P:P solution were added thereto, respectively, to obtain (3 wt%) PVA-P:P solutions of different concentrations, namely: (3 wt%) PVA-P:P (0 wt%), (3 wt%) PVA-P:P (3 wt%), (3 wt%) PVA-P:P (9 wt%), (3 wt%) PVA-P:P (15 wt%) and (3 wt%) PVA-P:P (25 wt%).
[0051] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above-mentioned different concentrations of (3 wt%) PVA-P:P solution, and after standing for 24 hours, a borate cross-linked hydrogel was formed, and then these cross-linked hydrogels were placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain different concentrations of (3 wt%) PVA-P:P hydrogel.
[0052] (4) Preparation of PVA (8 wt%)-P:P (15 wt%) hydrogel:
[0053] 0.869 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare an 8 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 8 wt% PVA solution was taken and 0.353 mL of the P:P solution was added thereto to obtain an (8 wt%) PVA-P:P (15 wt%) solution.
[0054] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (8 wt%) PVA-P:P (15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a PVA (8 wt%)-P:P (15 wt%) hydrogel.
[0055] (5) Preparation of PVA (7 wt%)-P:P (15 wt%) hydrogel:
[0056] 0.753 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to obtain a 7 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 7 wt% PVA solution was taken and 0.353 mL of the P:P solution was added thereto to obtain a (7 wt%) PVA-P:P (15 wt%) solution.
[0057] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (7 wt%) PVA-P:P (15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a PVA (7 wt%)-P:P (15 wt%) hydrogel.
[0058] (6) Preparation of PVA (6 wt%)-P:P (15 wt%) hydrogel:
[0059] 0.638 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to obtain a 6 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 6 wt% PVA solution was taken and 0.353 mL of the P:P solution was added thereto to obtain a (6 wt%) PVA-P:P (15 wt%) solution.
[0060] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (6 wt%) PVA-P:P (15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a PVA (6 wt%)-P:P (15 wt%) hydrogel.
[0061] (7) Preparation of PVA (5 wt%)-P:P (15 wt%) hydrogel:
[0062] 0.526 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 5 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 5 wt% PVA solution was taken and 0.353 mL of the P:P solution was added thereto to obtain a (5 wt%) PVA-P:P (15 wt%) solution.
[0063] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (5 wt%) PVA-P:P (15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a PVA (5 wt%)-P:P (15 wt%) hydrogel.
[0064] (8) Preparation of PVA (4 wt%)-P:P (15 wt%) hydrogel:
[0065] 0.417 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to obtain a 4 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 4 wt% PVA solution was taken and 0.353 mL of the P:P solution was added thereto to obtain a (4 wt%) PVA-P:P (15 wt%) solution.
[0066] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (4 wt%) PVA-P:P (15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a PVA (4 wt%)-P:P (15 wt%) hydrogel.
[0067] (9) Preparation of (HCPB)@PVA (3 wt%) hydrogel:
[0068] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken and 1 mL of HCPB (1 mg / mL) solution was added thereto to obtain a (HCPB)@PVA (3 wt%) solution.
[0069] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (HCPB)@PVA (3 wt%) solution, and after standing for 24 hours, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20°C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain a (HCPB)@PVA (3 wt%) hydrogel.
[0070] (10) Preparation of HCPB@PVA (3 wt%)-P:P (15 wt%) hydrogel:
[0071] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken, and 0.353 mL of the P:P solution and 1 mL of the HCPB (1 mg / mL) solution were added thereto to obtain a HCPB@PVA (3 wt%)-P:P (15 wt%) solution.
[0072] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above HCPB@PVA (3 wt%)-P:P (15 wt%) solution, and after standing for 24 hours, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20°C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain HCPB@PVA (3 wt%)-P:P (15 wt%) hydrogel.
[0073] (11) Preparation of (HCPB)QCSNE@PVA hydrogel:
[0074] 2.28 g of Tween-80 and 4.55 g of Span-80 were mixed as emulsifiers, 2.28 g of soybean oil was added as the oil phase, and the mixture was stirred at 450 rpm for 15 minutes. Subsequently, 0.662 mL (1 mg / mL) of HCPB solution and 0.228 g (10 wt%) of chitosan quaternary ammonium salt (QCS) solution were added dropwise, and the mixture was stirred at 800 rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain a (HCPB) QCSNE microsphere solution.
[0075] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken and 1 mL of the (HCPB)QCSNE microsphere solution was added thereto to obtain a (HCPB)QCSNE@PVA (3 wt%) solution.
[0076] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (HCPB)QCSNE@PVA (3 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain (HCPB)QCSNE@PVA (3 wt%) hydrogel.
[0077] (12) A method for preparing a low voltage driven conductive hydrogel, as follows:
[0078] Preparation of (HCPB)QCSNE microsphere solution:
[0079] 2.28g of Tween-80 and 4.55g of Span-80 were mixed as emulsifiers, 2.28g of soybean oil was added as the oil phase, and the mixture was stirred at 450rpm for 15 minutes. Subsequently, 0.662mL (1mg / mL) of HCPB solution and 0.228g (10wt%) of chitosan quaternary ammonium salt (QCS) solution were added dropwise, stirred at 800rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain a quaternary ammonium modified nanoemulsion (HCPB) QCSNE microsphere solution loaded with HCPB.
[0080] Preparation of (HCPB)QCSNE@PVA-P:P hydrogel:
[0081] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature. Then, 2 mL of the 3 wt% PVA solution was taken, and 0.353 mL of the P:P solution and 1 mL of the (HCPB)QCSNE microsphere solution were added thereto to obtain a (HCPB)QCSNE@PVA (3 wt%)-P:P (15 wt%) solution.
[0082] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (HCPB)QCSNE@PVA(3 wt%)-P:P(15 wt%) solution, and after standing for 24 h, a borate cross-linked hydrogel was formed, and then the cross-linked hydrogel was placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain (HCPB)QCSNE@PVA(3 wt%)-P:P(15 wt%) hydrogel.
[0083] (13) A method for preparing a low voltage driven conductive hydrogel, as follows:
[0084] Preparation of (DOX)QCSNE microsphere solution:
[0085] 2.28g Tween-80 and 4.55g Span-80 were mixed as emulsifiers, 2.28g soybean oil was added as the oil phase, and stirred at 450rpm for 15 minutes. Subsequently, 0.662mL (1mg / mL) of DOX solution and 0.228g (10wt%) of chitosan quaternary ammonium salt (QCS) solution were added dropwise, stirred at 800rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain a DOX-loaded chitosan quaternary ammonium modified nanoemulsion (DOX) QCSNE microsphere solution.
[0086] Preparation of (DOX)QCSNE@PVA-P:P hydrogel:
[0087] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken, and 0.353 mL of the P:P solution and 1 mL of the (DOX)QCSNE microsphere solution were added thereto to obtain a (DOX)QCSNE@PVA (3 wt%)-P:P (15 wt%) solution.
[0088] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (DOX)QCSNE@PVA (3 wt%)-P:P (15 wt%) solution, and the hydrogel was formed after standing for 24 h with borate crosslinking. These hydrogels were then placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 °C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain (DOX)QCSNE@PVA (3 wt%)-P:P (15 wt%) hydrogel.
[0089] (14) A method for preparing a low voltage driven conductive hydrogel, as follows:
[0090] (RB) Preparation of QCSNE microsphere solution:
[0091] 2.28g Tween-80 and 4.55g Span-80 were mixed as emulsifiers, 2.28g soybean oil was added as the oil phase, and stirred at 450rpm for 15 minutes. Subsequently, 0.662mL (1mg / mL) of RB solution and 0.228g (10wt%) of chitosan quaternary ammonium salt (QCS) solution were added dropwise, stirred at 800rpm for 20 minutes, ultrasonicated for 25 minutes, and allowed to stand for 120 minutes to obtain a quaternary ammonium modified nanoemulsion (RB) QCSNE microsphere solution loaded with RB.
[0092] Preparation of (RB)QCSNE@PVA-P:P hydrogel:
[0093] 0.310 g of PVA powder was added to 10 mL of deionized water and dissolved at 90°C to prepare a 3 wt% PVA solution, which was then cooled to room temperature; then 2 mL of the 3 wt% PVA solution was taken, and 0.353 mL of the P:P solution and 1 mL of the (RB)QCSNE microsphere solution were added thereto to obtain a (RB)QCSNE@PVA (3 wt%)-P:P (15 wt%) solution.
[0094] After that, 0.4 mL (3 wt%) Na2B4O7 solution was added to the above (RB) QCSNE@PVA (3 wt%)-P:P (15 wt%) solution, and the hydrogel was formed after standing for 24 h with borate crosslinking. These hydrogels were then placed in a polytetrafluoroethylene (PTFE) mold to form a regular quadrilateral hydrogel film. Then, a freeze-thaw cycle was performed, freezing at -20 ° C for 8 hours, thawing at room temperature for 2 hours, and the cycle was repeated 3 times to obtain (RB) QCSNE@PVA (3 wt%)-P:P (15 wt%) hydrogel.
[0095] The above materials were subjected to the following structural, morphological characterization and performance tests:
[0096] (1) Structural and morphological characterization
[0097] Dilute the NE microspheres to 10% in deionized water. -3 M, at pH = 7.4, room temperature, using Malvern ZetasizerNanoZS90 to test the hydrated particle size (DLS) and Zeta potential. Transmission electron microscopy (TEM, FEITecnaiF20) was used to observe NE and QCSNE microspheres. First, pure water at 30°C was dropped into it and gently stirred to make the emulsion self-emulsified to obtain a milky white emulsion. The emulsion was dropped onto a copper mesh covered with a support membrane, allowed to stand for 10 to 18 minutes, dried with filter paper, and then 3% phosphotungstic acid solution was added to the copper mesh for negative staining for 5 minutes, dried naturally, and then observed with TEM. The hydrogel was freeze-dried for 3 days. Then, the surface microstructure of the freeze-dried hydrogel was observed with a scanning electron microscope (SEM, JSM-IT500HR) at an accelerating voltage of 5kV. The pore size distribution was calculated using NanoMeasurer software. The chemical structure of the freeze-dried hydrogel was analyzed using an IRTrace-100 Fourier transform infrared spectrometer (FTIR) with a resolution of 4cm -1 , range is 4000cm -1 ~500cm -1 .
[0098] (2) Rheological test
[0099] Rheological tests were performed using a rheometer (HAAKE MARS60). The rheological test of the hydrogel included the following steps:
[0100] ① Time scans were performed to evaluate the stability of the hydrogels, with a strain of 1% and a frequency of 1 Hz for 30 min.
[0101] ② Determine the changes in the storage modulus (G') and loss modulus (G") of the hydrogel in the critical strain region and the linear viscoelastic region. The specific parameters are achieved by changing the dynamic strain of the hydrogel from 0.01% to 3000% at a frequency of ω=10rad / s.
[0102] ③ Study the self-healing properties of the hydrogel. The changes in the storage modulus (G') and loss modulus (G") of the hydrogel were investigated under alternating strains in the strain range of 1% and 800%, which included maintaining a low strain of 1% for 200 seconds, then maintaining a high strain of 800% for 60 seconds, and repeating 5 cycles.
[0103] (3) Self-healing performance test
[0104] To study the self-healing properties of the hydrogel, we cut the hydrogel in half and brought it close together to observe its self-healing behavior. In addition, we used an optical microscope (Olympus, Japan) to study the microscopic morphology of self-healing. We used LED to detect whether the self-healing properties had an effect on conductivity, and after cutting and merging the self-healing hydrogel, we observed the brightness of the small bulb in the circuit.
[0105] (4) Electrochemical performance test
[0106] The conductivity was measured using an ST2242 AC four-point probe conductivity meter (Suzhou Jingge Electronics Co., Ltd.). CV, EIS and it were measured using an electrochemical workstation (CHI760E). In-situ Raman measurements were performed using a C031-1 in-situ Raman electrolytic cell, with Pt wire as the counter electrode, Ag / AgCl as the reference electrode, and hydrogel as the working electrode, using the it mode of the electrochemical workstation as the electric field input.
[0107] (5) Release of guest molecules from hydrogels under electrical stimulation
[0108] A dual-electrode structure was used, with HCPB as a model molecule. A UV-visible spectrophotometer (Shimadzu, UV3600) was used to plot standard concentration-absorbance curves of HCPB at different concentrations. (HCPB)QCSNE microspheres were loaded into the hydrogel and placed on a titanium sheet as a working electrode, and a platinum wire was used as a counter electrode. PBS (pH = 7.4, 25°C) was used as the electrolyte, and the titanium sheet containing the hydrogel was placed at the positive electrode. A DC voltage regulator (MAISHENG, MS155D) was used to apply a constant DC voltage for 120 minutes, and the release liquid was extracted every 20 minutes, and then the same volume of PBS solution was introduced. The release rate of the hydrogel was determined according to formula (a). The absorbance at 280nm was measured using a UV-visible spectrophotometer for quantification. The experiment was repeated at least three times.
[0109]
[0110] In formula (a), M is the cumulative release rate of the molecule, C n is the concentration of the sample, V is the volume of the release medium, V i is the volume of the sample taken at the i-th time point, C i is the concentration of the sample taken at the i-th time point, and W is the mass of the molecule.
[0111] Figure 1Figure 1 is a structural and morphological characterization diagram of NE, QCSNE, PVA-P:P and QCSNE@PVA-P:P, where (a) is the DLS particle size, (b) is the Zeta potential, (c) is the TEM image of (i) NE and (ii) QCSNE, (d) is the SEM image of PVA (3wt%) hydrogel, (e) is the SEM image of PVA (3wt%)-P:P (15wt%), (f) is the FTIR spectra of PVA, P:P, and PVA-P:P, and (g) is the FTIR spectra of QCS, NE, QCSNE and QCSNE@PVA:PP. Figure 1 As shown in Figure 1, chitosan is first modified with quaternary ammonium groups to give it a permanent positive charge; thus, this facilitates strong electrostatic interactions with components with an overall negative charge compared to unmodified chitosan. NE microspheres can be prepared by adjusting the oil / water ratio using emulsifiers (Tween-80 and Span-80). Dynamic light scattering (DLS) showed that the particle size of NE microspheres was approximately 294 nm ( Figure 1 a). Since the oil phase contains negatively charged phosphate groups, it can be modified with quaternary ammonium salts to obtain QCSNE microspheres with positive surface charges ( Figure 1 b), which lays the foundation for loading guest molecules. Transmission electron microscopy (TEM) results show that the particle size of the microspheres does not change significantly from NE to QCSNE ( Figure 1 c), which is consistent with the DLS results. Since PVA hydrogels are prepared by borate crosslinking, this results in a high crosslinking density and improved mechanical properties, but this is usually accompanied by a loss of pores, which limits their effectiveness in guest molecule delivery. In this example, a low concentration of PVA (3wt%) was used to prepare borate crosslinked dynamic self-healing hydrogels. In addition, a freeze-thaw strategy (freezing at -20°C for 8 hours, thawing at room temperature for 2 hours, repeated 3 times) was used to introduce more crystalline domains into the hydrogel, enhancing its stability without changing the chemical structure. The crosslinking density of the conductive hydrogel is adjusted by using the sulfonic acid groups of PSS to form hydrogen bonding interactions with the hydroxyl groups in PVA to achieve the adjustment of the pore size (see Figure 1 d. Figure 1 e. Figure 2 ). Figure 2The SEM images of freeze-dried PVA and PVA-P:P hydrogels with different concentrations, wherein (a) is the SEM image of PVA (8wt%), (b) is the SEM image of PVA (8wt%)-P:P (15wt%), (c) is the SEM image of PVA (7wt%), (d) is the SEM image of PVA (7wt%)-P:P (15wt%), (e) is the SEM image of PVA (6wt%), (f) is the SEM image of PVA (6wt%)-P:P (15wt%), (g) is the SEM image of PVA (5wt%), (h) is the SEM image of PVA (5wt%)-P:P (15wt%), (i) is the SEM image of PVA (4wt%), and (j) is the SEM image of PVA (4wt%)-P:P (15wt%). Figure 1 d. Figure 1 e. Figure 2 In the SEM images, it can be observed that the decrease in PVA concentration leads to a gradual increase in pore size; in addition, the incorporation of P:P further optimizes the pore structure by affecting the crosslinking density. Fourier transform infrared (FTIR) spectroscopy verifies the presence of functional groups in the composite hydrogel and detects the interactions between the components ( Figure 1 f): For pure PVA, at 3371cm -1 The broad and strong peak at 3470 cm / s corresponds to the symmetric stretching vibration of the hydroxyl group. The hydroxyl stretching vibration peak of PVA-P:P shifts to a lower wave number (3351 cm / s). -1 ) moved, indicating that the borate bonds between PVA chains were weakened by the interaction with P:P. In addition, P:P provided negative charges for the positively charged QCSNE microspheres, and FTIR further revealed the interaction between NE microspheres and hydrogels ( Figure 1 g):1480cm in QCS -1 The peak at -(CH3)3N + The peak is shifted to 1474 cm in QCSNE@PVA-P:P due to the CH vibration of -1 , confirming the electrostatic interaction with PVA-P:P hydrogel; the main oil phase component of NE, lecithin, was at 1242 cm -1 The characteristic peak of the P=O group appeared at 1235 cm-1. In the QCSNE spectrum, it shifted to 1235 cm-1 due to the electrostatic interaction between the amino group of QCS and the phosphate group of lecithin. -1 The above results indicate that the introduction of P:P not only regulates the pore size of PVA hydrogels, but also provides negatively charged functional units (PSS) for constructing the controllable delivery mechanism of QCSNE microspheres.
[0112] Figure 3The self-healing and conductive properties of PVA-P:P hydrogels, where (a) is a digital photo of the PVA (3wt%) (transparent) and PVA (3wt%)-P:P (15wt%) (dark blue) hydrogels merged together, (b) is a microscopic photo of the hydrogel self-healing process (scale: 1μm), (c) is the conductivity of hydrogels with different P:P concentrations and the strain and modulus at the flow point, (d) is the EIS of hydrogels with different P:P concentrations, (e) is the CSC of hydrogels with different P:P concentrations, (f) is the current change before and after the hydrogel is cut, and (g) is a digital photo of the impact of the (HCPB)QCSNE@PVA (3wt%)-P:P (15wt%) hydrogel fracture and self-healing on the circuit. Figure 3 As shown in Figure 2, the self-healing behavior of the PVA-P:P hydrogel was confirmed by reassembling two cut hydrogel sheets, and the healing process was observed to occur within a few seconds after the hydrogels came into contact ( Figure 3 a). In addition, the self-healing process was observed from the microscopic perspective of the hydrogel. The cracks formed at the junction of the two cut hydrogels disappeared after 0.5 hours and completely disappeared after 1 hour ( Figure 3 b). PVA (3wt%) and PVA (3wt%)-P:P (15wt%) hydrogels were subjected to alternating scans of 1% strain for 200 seconds and 800% strain for 60 seconds, respectively, and repeated for 5 cycles. The results showed that its modulus quickly recovered to its initial value, implying that it has excellent self-healing ability. The self-healing property of PVA-P:P hydrogel is mainly attributed to the borate ester bonds between borate and PVA, and the hydrogen bonds within and between PVA. Based on this self-healing property, the conductivity of the hydrogel was measured using a four-probe resistivity meter, and it was found that the addition of P:P to the PVA hydrogel significantly improved its conductivity; however, with the increase of P:P content, the flow point strain shifted, and when the P:P concentration was 25wt%, G” in the strain scanning range began to exceed G’, suggesting that it had undergone a transition from gel to sol. Figure 3 c shows that the conductivity of the hydrogel is 1.31 S m when the P:P concentration is 15 wt%. -1 , and the strain and modulus at the flow point reached 362.28% and 49.95Pa, showing good conductivity, machinability and stability. The results of electrical impedance spectroscopy (EIS) showed that with the increase of P:P concentration, the charge transfer resistance (R ct ) significantly reduced ( Figure 3 d). Charge storage capacity (CSC) is an important indicator of bioelectronic response. It can be seen that CSC increases with the increase of P:P content. This improvement in charge injection capacity further reflects its excellent electrical properties ( Figure 3e). In addition, the conductive properties were evaluated in combination with the self-healing process. A series of current-time tests over several cycles showed that the hydrogel had an excellent self-healing effect ( Figure 3 f). In addition, a light-emitting diode (LED) was connected to the circuit, and its light emission went out when the (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel was cut in half; however, when the two segments of the (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel were reconnected, the LED quickly re-emitted light, indicating that the hydrogel still had high conductivity after self-healing ( Figure 3 g).
[0113] Based on the structural characteristics of NE microspheres and PVA-P:P hydrogels, a controllable guest molecule delivery system was designed. Since PSS is hydrophilic in the P:P structure and PEDOT is hydrophobic, the outside of the P:P polymer chain will be negatively charged, and this property was used to achieve the controlled release of the positively charged QCSNE microspheres. Figure 4 Figure 2 shows the results of electric field-controlled guest molecule release, where (a) is the release of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V or 0V (the inset is the chemical structure of HCPB), (b) is the ON / OFF voltage release curve of (HCPB)QCSNE@PVA(3wt%) and (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at an interval of 20 minutes, (c) is a brief comparison of the molecular release curves of different hydrogels after 120 minutes of electrical stimulation, and (d) is the ON / OFF voltage release curve of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at an interval of 10 minutes. t%) hydrogel under 1.5V electric field, (e) is the relative ratio change of hydrogen bonding signal (corresponding to the change of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel when 1.5V voltage is alternately applied for 10 minutes and off for 10 minutes), (f) is the SEM image of freeze-dried PVA(3wt%)-P:P(15wt%) after (i) no application and (ii) 1.5V voltage is applied for 120 minutes, (g) is the pore size distribution histogram of PVA(3wt%)-P:P(15wt%) when voltage is applied / not applied, (h) is the in situ Raman shift change of SO during repeated electrical stimulation cycles. Initially, the model guest molecule, hexa(4-carboxy-1-phenylthio)benzene, named HCPB, was loaded into the cavity of QCSNE microspheres to form (HCPB)QCSNE (chemical structure of HCPB, see Figure 4 aIllustration.)
[0114] Figure 5 The UV-Vis spectra of different HCPB concentrations (with PBS as solvent) and the HCPB concentration-absorbance standard curve, where (a) is the UV-Vis spectra of different HCPB concentrations (with PBS as solvent), and (b) is the HCPB concentration-absorbance standard curve. Figure 5 As shown, the UV-visible spectrum shows the absorption change of HCPB at 280 nm at different concentrations, and a standard curve of its concentration and absorbance is obtained for calibrating the undetermined concentration.
[0115] Subsequently, these HCPB-loaded QCSNE microspheres were incorporated into PVA-P:P hydrogels through electrostatic interactions, which enhanced the stability of guest molecule loading. At 1.5 V, the release of (HCPB)QCSNE@PVA (3 wt%)-P:P (15 wt%) hydrogel exceeded 39%, while at 0 V, only 7% ( Figure 4 a).
[0116] Figure 6 (a) Release curve and (b) Korsmeyer-Peppas fitting curve of (HCPB)QCSNE@PVA (3 wt%) hydrogel at 0 V. Figure 6 As shown in the figure, in the absence of an electric field, the release amount of (HCPB)QCSNE@PVA(3wt%) hydrogel is only 7.5% compared with that of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel, which also indicates that the presence of P:P stabilizes the release of guest molecules through electrostatic attraction.
[0117] By periodically applying a voltage of 1.5 V, the (HCPB)QCSNE@PVA (3 wt%)-P:P (15 wt%) hydrogel achieved pulsed release of guest molecules; while for the (HCPB)QCSNE@PVA (3 wt%) hydrogel, it had a stable release profile with or without electric field input ( Figure 4 b).
[0118] like Figure 7 As shown, Figure 7 The Korsmeyer-Peppas fitting curve of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V / 0V voltage. The release kinetics of (HCPB)QCSNE@PVA-P:P hydrogel under the action of electric field conforms to the Korsmeyer-Peppas model, showing a non-Fickian diffusion mechanism (see Table 1, Figure 7), indicating that its release behavior is affected by the changes in the main chain and other interactions within the hydrogel. In contrast, the addition of guest molecules to the hydrogel without QCSNE microspheres resulted in insufficient controllability of delivery due to electrostatic interactions: the 0 V release index n was 0.8697, which was higher than 0.7609 of QCSNE microspheres.
[0119] Table 1 Release parameters of each hydrogel
[0120]
[0121] By applying the Korsmeyer-Peppas model, the release kinetics of the guest molecules from the gel within time t can be elucidated:
[0122]
[0123] Among them, M t / M ∞ represents the amount of HCPB released at time t, and k represents the kinetic constant of the guest molecule transport system. n values equal to or less than 0.5 represent Fickian diffusion, while values between 0.5 and 1 represent non-Fickian diffusion.
[0124] Although hydrogels have superior biocompatibility and biodegradability compared to conductive polymers, they generally require higher voltages (2-25V). In contrast, conductive polymers can function effectively at significantly lower voltages (0.5-3V). By integrating the advantages of hydrogels and conductive polymers, high-voltage and low-voltage regions can be delineated. Therefore, the QCSNE@PVA-P:P hydrogel in this example (HCPB) has significant advantages in controlled delivery in low-voltage regions ( Figure 4 c). In addition, unlike other delivery systems, our strategy is flexible and generally applicable and is not limited to specific materials or guest molecules. A range of guest molecules, including drugs (e.g., DOX) and fluorescent probes (e.g., RB), can be delivered quickly and precisely using this approach.
[0125] Figure 8 UV-visible spectra of DOX and RB (PBS as solvent) with different concentrations and concentration-absorbance standard curves of DOX and RB, where (a, c) are UV-visible spectra of DOX and RB (PBS as solvent) with different concentrations, and (b, d) are concentration-absorbance standard curves of DOX and RB. Fig. 9The release curves of (DOX)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel and (RB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V and their Korsmeyer-Peppas fitting curves, where (a) is the release curve of (DOX)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V, (b) is the release curve of (RB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel at 1.5V, and (c) is the Korsmeyer-Peppas fitting curve of (a) and (b). Figure 8 , Fig. 9 As shown in Figure 2, the concentration-absorbance relationship was established by UV-visible spectroscopy. After 120 minutes of continuous action at 1.5V low voltage, the cumulative release rates of DOX and RB reached 44.72% and 48.32%, respectively. The release kinetics were similar to those of HCPB ( Fig. 9 , Table 2), so the (DOX)QCSNE@PVA-P:P hydrogel and (RB)QCSNE@PVA-P:P hydrogel in this example also have significant advantages in the controlled delivery of low-pressure areas. The above results show that the building blocks we designed on NE microspheres and PVA hydrogels have become versatile tools to promote the controlled delivery of guest molecules.
[0126] Table 2 Release parameters of DOX and RB from hydrogels
[0127]
[0128]
[0129] In order to explore the mechanism of release by electrical stimulation, e.g. Figure 4 In situ Raman spectra (d) reveal the changes in the interactions of (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel during the release process. 3000cm -1 ~3800cm -1 The main broad peaks in the range are generated by the hydroxyl vibration of H2O in the hydrogel system; specifically, 3240 cm -1 The strong hydrogen bond between PVA and H2O is shown at 3400 cm -1 The peak at represents the weak hydrogen bonds formed between H2O molecules.
[0130] like Figure 4As shown in Figure e, by alternately applying 1.5V for 10 minutes and then turning it off for 10 minutes, the proportion of strong hydrogen bond signals in the (HCPB)QCSNE@PVA(3wt%)-P:P(15wt%) hydrogel increased, while for the (HCPB)QCSNE@PVA(3wt%) hydrogel, this effect was not obvious. This trend of enhanced hydrogen bond interaction between PVA and H2O in turn indicates that the hydrogen bond interaction between PVA and P:P is weakened under the action of the electric field. Therefore, the hydrogel structure is transformed from a regular porous network to a network with larger pores ( Figure 4 f), the average pore size increased from 21.63 μm to 33.61 μm, which is beneficial for the delivery of guest molecules ( Figure 4 g).
[0131] In addition, at 1080cm -1 SO 3- The peak of the SO group underwent a reversible blue shift under the action of the electric field, confirming that the electrostatic interaction between the positively charged (HCPB)QCSNE microspheres and the negatively charged PVA (3wt%)-P:P (15wt%) hydrogel can be repeatedly weakened and reorganized by electrostatic attraction and repulsion ( Figure 4 h). When the chemical structure of the polymer components before and after electrical stimulation was analyzed by FTIR, no significant changes in the vibration peaks were found. This fact indicates that this is a purely physical transfer mechanism without chemical reactions. After 120 minutes of continuous voltage application, the pH value of the system remained stable at around 7.4, indicating that the change in pH value did not produce additional effects. By applying negative voltages of -5V and -1V for 120 minutes, it was found that there was no significant effect on the release of HCPB, DOX, and RB, further confirming that the transmission depends on electrostatic repulsion rather than electrophoretic effect. Therefore, compared with other electrically controlled delivery mechanisms, the present invention achieves efficient and controllable guest transport through the joint regulation of host-guest electrostatic repulsion and non-covalent hydrogen bonds induced by electric fields. In addition, the (Guest) QCSNE@PVA-P:P hydrogel release system of the present invention can operate efficiently at a low threshold voltage (only 0.5V), further proving that the release system achieves precise and controllable release in the low-pressure region; however, high voltage (5V or even 10V) will cause irreversible damage to the release system.
[0132] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A low voltage driven conductive hydrogel, characterized in that: The raw materials of the conductive hydrogel include the following components in percentage by weight: The balance is water.
2. A low voltage driven conductive hydrogel according to claim 1, characterized in that: The guest molecule is selected from any one of luminescent molecules, drugs or organic fluorescent probes.
3. A low voltage driven conductive hydrogel according to claim 2, characterized in that: The luminescent molecule is hexa(4-carboxy-1-phenylthio)benzene (HCPB) or sodium tetraphenylethylene sulfonate; the drug is selected from any one of doxorubicin (DOX), oxacillin or acyclovir; and the organic fluorescent probe is selected from any one of rhodamine B (RB), fluorescein isothiocyanate or methylene blue.
4. A low voltage driven conductive hydrogel according to claim 1, characterized in that: The emulsifier is selected from at least one of Tween-80, Span-80, sodium lauryl sulfate or polyoxyethylene stearate.
5. The low-voltage driven conductive hydrogel according to claim 1, characterized in that: The oil is selected from any one of soybean oil, sunflower seed oil, almond oil or coconut oil.
6. A method for preparing a low-voltage driven conductive hydrogel according to any one of claims 1 to 5, characterized in that: The steps include: S1, uniformly mixing the emulsifier and the oil, then slowly adding a mixed solution of quaternary ammonium salt chitosan, guest molecules and a portion of water into the mixture of the emulsifier and the oil, stirring, ultrasonicating and standing to obtain a positively charged guest molecule nanoemulsion microsphere solution; S2, completely dissolving the PVA powder in another portion of water to obtain a PVA aqueous solution, adding PEDOT:PSS and the guest molecule nanoemulsion microsphere solution obtained in step S1 to the PVA aqueous solution after cooling to room temperature, mixing evenly to form a conductive hydrogel precursor, adding Na2B4O7 for chemical cross-linking and then standing, and then cyclically freezing and thawing to obtain a low-voltage driven conductive hydrogel.
7. A low voltage driven conductive hydrogel according to claim 6, characterized in that: In step S2, PVA powder is completely dissolved in water at a temperature of 80°C to 100°C.
8. The low-voltage driven conductive hydrogel according to claim 6, characterized in that: The mass ratio of the water used to dissolve the quaternary ammonium salt chitosan and the guest molecules in step S1 to the water used to dissolve the PVA powder in step S2 is 1:(2.5-3.5).
9. The low-voltage driven conductive hydrogel according to claim 6, characterized in that: In step S2, the freeze-thaw cycle is specifically as follows: freezing the stationary chemically cross-linked conductive hydrogel precursor at -40°C to -20°C for 4 to 12 hours, then taking it out and thawing it at a temperature not lower than 20°C for 2 to 4 hours, and the freeze-thaw process is repeated 3 to 5 times.
10. Use of the low-voltage driven conductive hydrogel according to any one of claims 1 to 5 in tissue engineering and drug delivery.